At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Select the correct answer.

What is the solution for [tex]x[/tex] in the equation?
[tex]-11x - 30 + 6x = 0[/tex]

A. [tex]x = \frac{30}{17}[/tex]

B. [tex]x = -6[/tex]

C. [tex]x = -\frac{30}{17}[/tex]

D. [tex]x = 6[/tex]


Sagot :

To solve the equation [tex]\(-11x - 30 + 6x = 0\)[/tex] for [tex]\(x\)[/tex], follow these steps:

1. Combine like terms:
[tex]\[ -11x + 6x - 30 = 0 \][/tex]
Combine the [tex]\(x\)[/tex] terms:
[tex]\[ -5x - 30 = 0 \][/tex]

2. Isolate the [tex]\(x\)[/tex] term:
To do this, first move the constant term (in this case, [tex]\(-30\)[/tex]) to the other side of the equation. You achieve this by adding 30 to both sides:
[tex]\[ -5x - 30 + 30 = 0 + 30 \][/tex]
Simplifies to:
[tex]\[ -5x = 30 \][/tex]

3. Solve for [tex]\(x\)[/tex]:
Divide both sides by [tex]\(-5\)[/tex]:
[tex]\[ x = \frac{30}{-5} \][/tex]
Simplifies to:
[tex]\[ x = -6 \][/tex]

Therefore, the solution to the equation [tex]\(-11x - 30 + 6x = 0\)[/tex] is [tex]\(x = -6\)[/tex].

So, the correct answer is:

B. [tex]\(x = -6\)[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.